Increasing antimicrobial resistance to clarithromycin and metronidazole in pediatric Helicobacter pylori infection in southern Taiwan: A comparison between two decades. Issue 5 (11th July 2019) - Lu, Hsiao‐Han; Lai, Fu‐Ping; Lo, Hsiao‐Yu; Sheu, Bor‐Shyang; Yang, Yao‐Jong
Abstract: Background: Antimicrobial resistance of Helicobacter pylori reduces the eradication rate. This study aimed to investigate changes in antimicrobial susceptibility of H pylori isolated from children in Taiwan in the past two decades. Methods: This study enrolled children receiving esophagogastroduodenoscopy for upper gastrointestinal diseases in a national tertiary referring hospital from 1998 to 2018. H pylori infection was diagnosed by culture. The minimal inhibitory concentrations (MICs) of antibiotics were tested using the E test. The antibiotic resistance rates and MICs of amoxicillin, clarithromycin, metronidazole, levofloxacin, and tetracycline were compared between 1998‐2008 and 2009‐2018. Results: A total of 70 Helicobacter pylori isolates (29 from 1998 to 2008 and 41 from 2009 to 2018) were identified. The esophagogastroduodenoscopy findings included duodenal ulcers (n = 31), gastric ulcers (n = 9), and gastritis (n = 30). The overall antimicrobial resistance rates of clarithromycin and metronidazole were 22.9% and 21.4%, respectively. The dual resistance rate of clarithromycin and metronidazole was 10%. Resistance rates of levofloxacin and amoxicillin were 8.3% and 2.9%, respectively. None of the isolates were resistant to tetracycline. Compared with the isolates from 1998 to 2008, those from 2009 to 2018 had higher MICs and resistance rates of clarithromycin (26.8% vs 17.2%, P  = 0.35) and metronidazole (26.8% vs 13.8%, P  = 0.19), but not levofloxacin (9.8% vs 5.3%, P  = 1.0) or coresistance to clarithromycin and metronidazole (12.2% vs 6.9%, P  = 0.69). Conclusions: The antimicrobial resistance rates of pediatric H pylor i isolates to clarithromycin and metronidazole increased during the past decade. The selection of antimicrobial agents other than clarithromycin and metronidazole is crucial to increase pediatric H pylori eradication rates.